PENGARUH MODEL HANDS ON ACTIVITY TERHADAP HASIL BELAJAR IPA PADA KELAS V SD 4 GONDOSARI GEBOG KUDUS - Faizah Kusuma Ningrum, Noor; Rahmawati, Septina; Aufia Abshor, Devy; Cahya Rohim, Dhina; Aris Prasetiyanto, Moh (Pusat Pengembangan Pendidikan dan Penelitian Indonesia, 2025)
Improving science learning outcomes in elementary schools, particularly in rural areas with limited resources, remains a persistent challenge. At SD 4 Gondosari Gebog Kudus, instruction is still dominated by lecture-based methods, resulting in passive student participation and low academic achievement. This study aims to examine the effect of the Hands-On Activity model on the science learning outcomes of fifth-grade students. A quantitative approach was employed using a One Group Pretest-Posttest design. The sample consisted of 13 fifth-grade students, and the research instrument was a 20-item multiple-choice test that had been validated and tested for reliability. Data analysis included the Shapiro-Wilk test for normality, Levene’s test for homogeneity, simple linear regression, and paired sample t-test. The results showed an increase in the average score from 61.54 (pretest) to 82.69 (posttest), with the t-test yielding a significance value of p = 0.000 (< 0.05), indicating a significant effect of the Hands-On Activity model. These findings reinforce the effectiveness of active learning in enhancing students’ conceptual understanding and engagement, especially in resource-constrained educational environments. The Hands-On Activity model offers a contextual and practical alternative instructional strategy for elementary education. ABSTRAK Peningkatan hasil belajar IPA di sekolah dasar, khususnya di wilayah pedesaan dengan keterbatasan sarana, masih menjadi tantangan. Di SD 4 Gondosari Gebog Kudus, pembelajaran masih didominasi metode ceramah yang membuat siswa pasif dan berdampak pada rendahnya capaian akademik. Penelitian ini bertujuan untuk mengetahui pengaruh model Hands-On Activity terhadap hasil belajar IPA siswa kelas V. Penelitian menggunakan pendekatan kuantitatif dengan desain One Group Pretest-Posttest. Sampel terdiri dari 13 siswa kelas V, dengan instrumen tes pilihan ganda sebanyak 20 soal yang telah divalidasi dan diuji reliabilitasnya. Analisis data meliputi uji normalitas (Shapiro-Wilk), homogenitas (Levene), regresi sederhana, dan paired sample t-test. Hasil menunjukkan peningkatan skor rata-rata dari 61,54 (pretest) menjadi 82,69 (posttest), dengan uji t menghasilkan p = 0,000 (< 0,05), yang berarti terdapat pengaruh signifikan dari penggunaan model Hands-On Activity. Temuan ini memperkuat efektivitas pembelajaran aktif dalam meningkatkan pemahaman konsep IPA dan keterlibatan siswa di lingkungan belajar dengan sumber daya terbatas. Model ini dapat menjadi alternatif strategi pembelajaran yang kontekstual dan aplikatif di sekolah dasar.